Development of Spectral Hazard Map for Indonesia with a Return Period of 2500 Years using Probabilistic Method - Asrurifak M.; Irsyam M.; Budiono B.; Triyoso W.; Hendriyawan Hendriyawan (Institute of Research and Community Outreach - Petra Christian University, 2010)
This study is performed to develop spectral hazard map for Indonesia with a Return Period of 2500 years earthquake. It will be proposed for revision of the Indonesian hazard map in SNI-03-1726-2002 as response to the meeting organized by the Department of Public Works on 27- October-2008 in Jakarta. The meeting has decided to revise the Indonesia hazard map by referring to IBC-2006 where spectral acceleration values at Peak Ground Acceleration/PGA, 0.2 and 1.0 second with a return period of 2500 year will be applied for general buildings. The spectral hazard map was analyzed using total probability method and three dimensional (3-D) source models with recent seismotectonic parameters. Four source models were used in this analysis, namely: shallow background, deep background, fault, and subduction source models. Generally, the results of analysis show the values of PGA with a return period of 2500 years relatively higher 1.2-3.0 times than in SNI-03-1726-2002.